2015
DOI: 10.1093/molbev/msv168
|View full text |Cite
|
Sign up to set email alerts
|

The Genome Sequence ofSaccharomyces eubayanusand the Domestication of Lager-Brewing Yeasts

Abstract: The dramatic phenotypic changes that occur in organisms during domestication leave indelible imprints on their genomes. Although many domesticated plants and animals have been systematically compared with their wild genetic stocks, the molecular and genomic processes underlying fungal domestication have received less attention. Here, we present a nearly complete genome assembly for the recently described yeast species Saccharomyces eubayanus and compare it to the genomes of multiple domesticated alloploid hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
237
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(246 citation statements)
references
References 87 publications
(153 reference statements)
8
237
0
1
Order By: Relevance
“…Natural hybrids between many of the members of the Saccharomyces species complex have been identified [10, 11]. For example, Saccharomyces pastorianus formed at least twice from recent hybridizations between Saccharomyces cerevisiae and Saccharomyces eubayanus , and this event has been associated with the acquisition of cold tolerance in the lager yeast [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Natural hybrids between many of the members of the Saccharomyces species complex have been identified [10, 11]. For example, Saccharomyces pastorianus formed at least twice from recent hybridizations between Saccharomyces cerevisiae and Saccharomyces eubayanus , and this event has been associated with the acquisition of cold tolerance in the lager yeast [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Whereas it was generally assumed that lager yeasts were hybrids between S. cerevisiae and S. bayanus, Libkind et al (11) showed that the second parent is actually S. eubayanus, a species originally discovered in Patagonia but later also isolated in other regions, such as North America and China (11)(12)(13). Although conclusive molecular evidence is not available (14), it is currently believed that the S. cerevisiae/S. eubayanus hybridization event took place 500 to 600 years ago, when German laws forced brewers to use lower fermentation temperatures, promoting the selection of rare natural hybrids between the common brewer's yeast S. cerevisiae and the more cold-tolerant S. eubayanus (11,15).…”
mentioning
confidence: 99%
“…The first additional duplicate gene is GAL80B , which is a paralog of GAL80 ; this pair of paralogs was created by the whole genome duplication (WGD) event roughly 100 million years ago (Wolfe and Shields, 1997; Marcet-Houben and Gabaldón, 2015). GAL80B has been retained in the S. uvarum-Saccharomyces eubayanus clade, but it was lost in the S. cerevisiae - Saccharomyces arboricola clade (Hittinger et al, 2010, 2004; Scannell et al, 2011; Caudy et al, 2013; Hittinger, 2013; Liti et al, 2013; Baker et al, 2015). The second one is GAL2B , which was created by a recent tandem duplication in S. uvarum-S. eubayanus clade.…”
Section: Resultsmentioning
confidence: 99%
“…After the S. uvarum-S. eubayanus clade diverged from the S. arboricola-S. cerevisiae clade, these genes met distinct fates in different lineages (Figure 8). GAL80B was lost in the S. cerevisiae-S. arboricola clade, while it was retained in S. uvarum and S. eubayanus (Hittinger et al, 2010, 2004; Scannell et al, 2011; Caudy et al, 2013; Hittinger, 2013; Liti et al, 2013; Baker et al, 2015). The fates of GAL1 and GAL3 were still more varied.…”
Section: Discussionmentioning
confidence: 99%